Analisis Pengaruh Pengangguran terbuka dan Indeks Pembangunan Manusia terhadap Kemiskinan menurut kota di Provinsi Jawa Barat Priode 2017 - 2021 - Amiroh Amiroh (Journal of Management and Social Sciences, 2022)
Poverty is a complex problem that is still difficult to solve in almost all regions of Indonesia. Poverty is a measure of negative social conditions arising from increasing poverty. West Java is one of the areas that has a relatively high poverty rate and is increasing every year. It uses a panel data model with an estimated fixed effect model for 9 cities from 2017 to 2021. The purpose of this research is to analyze how and how much unemployment and HDI affect the poverty in West Java province. The data used is secondary data obtained from the Central Statistics Agency (BPS) which is processed. The results state that partially and simultaneously the unemployment variable and the human development index do not affect poverty.